Якість та безпечність м'яса свиней за застосування натуральних кормових добавок із вмістом Омега-3 жирних кислот і селену - Ткачик, Людмила Віталіївна (НУБіП України, 2021)
Дисертація на здобуття наукового ступеня кандидата ветеринарних наук зі спеціальності 16.00.09 «Ветеринарно-санітарна експертиза». Національний університет біоресурсів і природокористування України, Київ, 2021.Вперше зроблено науково-практичне обґрунтування якості та безпечності м’яса за застосування у годівлі свиней кормових добавок LG-MAX і Сел-Плекс, що містять натуральні компоненти. Вперше розроблено схему науково-господарського досліду із застосування кормових добавок LG-MAX і Сел-Плекс у годівлі відгодівельного молодняку свиней. Під час згодовування цих кормових добавок встановлено, що морфологічні та біохімічні показники сироватки крові свиней були у фізіологічних межах, відповідно віку дослідних тварин. Водночас, встановлено достовірне збільшення живої маси свиней, абсолютного, відносного та середньодобових приростів, забійної маси, довжини туші, площі «м’язового вічка» та товщини шпику і зменшення вологи у м’ясі та збільшення вмісту сухої речовини із одночасним збільшенням вмісту жиру, та протеїну. Органолептичні, фізико-хімічні показники свинини та підшкірного жиру і мікробіологічні показники м’яса відповідали вимогам нормативних документів. Разом із тим, за дегустаційною оцінкою свинини встановлено поліпшення її смакових якостей під час згодовування свиням 2,0 г/добу кормової добавки LGMAX. У свинині (за згодовування свиням 2,0 г/добу добавки LG-MAX) встановлено зменшення на 2,92 % співвідношення Омега-6 до Омега-3 поліненасичених жирних кислот. Застосування у годівлі свиней цих кормових добавок свідчить про відсутність токсичної дії препарату на м’ясо свиней (загибель інфузорій Tetraсhуmena pуriformis становила від 0,22 % до 0,38 %, а щільність їх росту – від 99,50 % до 99,78 %). За гістологічним дослідженням мікроструктури печінки свиней, яким згодовували 2,0 г/добу кормової добавки LG-MAX, встановили наявність незначних дистрофічних процесів у гепатоцитах. Натомість, зерниста і жирова інфільтративна дистрофії та гіперемія судин всередині часточки були виявлені в гепатоцитах печінки свиней, яким згодовували 4,0 г/добу кормової добавки LG-MAX і лімфогістіоцитарна інфільтрація строми – у печінці свиней, яким згодовували 2,0 г/добу кормової добавки LG-MAX разом із Сел-Плекс.
The dissertation on competition of a scientific degree of the candidate of veterinary sciences on a specialty 16.00.09 "Veterinary and sanitary examination". – National University of Life and Environmental Sciences of Ukraine, Kyiv, 2021.The dissertation for the first time addressed the topical issue of meat quality and safety for the use of feed additives LG-MAX and Sel-Plex, which contain natural components. For the first time, a scheme of scientific and economic experiment on the use of these feed additives in the feeding of fattening pigs has been developed. A control group of pigs and three experimental groups were created for the experiment: group D1 (2.0 g/day of LG-MAX supplement was fed to the main diet), group D2 (4.0 g/day of LG-MAX supplement was fed to the main diet), group D3 (LG-MAX and Sel-Plex supplements were fed to the main diet 2.0 g/day, according to the registration certificate). During the feeding of these feed additives, it was found that the morphological and biochemical parameters of pig serum were within physiological limits, according to the age of the experimental animals. At the same time, during feeding of pigs 2.0 g/day of feed additive LG-MAX, an increase in live weight of pigs by 4.92 % (p≤0.001), an absolute increase of 5.47 % (p≤0.001), a relative increase – by 0.97 %, average daily – by 5.47 % (p≤0.001), carcass weight by 5.31 % (p≤0.001), the length of the chilled carcass by 2.71 % (p≤0.001), the area of muscle eye "by 6.61 % (p≤0.001). During feeding of pigs 4.0 g/day of feed additive LG-MAX, an increase in live weight of pigs by 14.95 % (p≤0.001), an absolute increase of 17.05 % (p≤0.001), a relative increase of 5.06 %, the average daily – by 17.04 % (p≤0.001), carcass weight by 1.46 % (p≤0.001), the length of the carcass by 4.54 % (p≤0.001), the area of the "muscle cell" on 7.93 % (p≤0.001), fat thickness by 16.32 % (p≤0.001). During feeding of pigs 2.0 g/day of feed additive LG-MAX together with Sel- Plex, an increase in live weight of pigs by 7.79 % (p≤0.001), an absolute increase of 8.50% (p≤0.001), relative – by 1.83 %; average daily – by 8.51 % (p≤0.001), carcass weight by 9.05 % (p≤0.001), the length of the chilled carcass by 3.43 % (p≤0.001), the area of the "muscle cell" by 4, 99 % (p≤0.001) and fat thickness by 6.95 % (p≤0.001).Organoleptic and physicochemical parameters of pork met the requirements of regulations, which confirms the receipt of meat from healthy animals and the degree – fresh. According to the tasting evaluation of pork, an improvement in its taste was found during feeding of pigs with LG-MAX feed additive at a dose of 2.0 g/day. When feeding pigs 2.0 g/day of LG-MAX supplementation, an increase of 13.8 % (p<0.01) in fat content was found; for feeding pigs 4.0 g/day of LG-MAX additive - increase in dry matter content by 8.9 % (p<0.05), protein content – by 9.0 % (p<0.001) and fat content by 35 % (p<0.001) and a decrease in moisture by 6.45 % (p<0.05); for feeding pigs 2.0 g/day of LG-MAX supplement together with Sel-Plex – increase in protein content by 9.7 % (p<0.001) and fat by 14.8 % (p<0.01). In pork (for feeding pigs 2.0 g/day of LG-MAX supplement) the total amount of the Omega-3 polyunsaturated fatty acids was higher by 0.12 % and by 0.25 % – (for feeding pigs 4.0 g/day LG-MAX supplements). In pork (for feeding pigs 4.0 g/day of LG-MAX supplement) the total amount of the Omega-3 polyunsaturated fatty acids was higher by 0.13 % than for feeding pigs 2.0 g/day of LG-MAX supplement. At the same time, there was a decrease in the ratio of Omega-6 to Omega-3 polyunsaturated fatty acids by 2.92 % (when feeding pigs 2.0 g/day of LG-MAX supplement) and by 5.59 % (when feeding pigs 4.0 g/day) LG-MAX supplements). Also, in pork (for feeding pigs 2.0 g/day supplement LG-MAX together with Sel-Plex) found an increase in the amount of the Omega-3 and Omega-6 polyunsaturated fatty acids, respectively, by 0.1 % and 3.02 %, which led to an increase in the ratio of Omega-6 to Omega-3 polyunsaturated fatty acids by 2.9 %. The studied physicochemical parameters of subcutaneous fat of pigs met the requirements of regulatory documents. According to the conducted microbiological researches the conformity of pork of experimental and control groups to requirements of the current regulatory documents is established. At the same time, the rate of the number of mesophilic aerobic and facultatively anaerobic microorganisms in pork (for feeding pigs 2.0 g/day of LG-MAX supplement) was lower by 73.1 % (p<0.001) and by 71.6 % (p<0.001) (for feeding pigs 2.0 g/day of LG-MAX supplement together with Sel-Plex). The use of these feed additives in pig feeding led to the death of Tetrashymena pуriformis ciliates from 0.22 % to 0.38 %, their dense growth from 99.50 % to 99.78 %, which indicates the absence of toxic effects of the drug on pig meat. Histological examination of the microstructure of the liver of pigs fed 2.0 g/day of LG-MAX feed additive revealed the presence of minor dystrophic processes in hepatocytes. In contrast, granular and fatty infiltrative dystrophy and intra-lobe vascular hyperemia were detected in porcine liver hepatocytes fed 4.0 g/day of LG-MAX feed additive and lymphohistiocytic infiltration of the stroma in pig liver fed 2.0 g/day of feed. LG-MAX supplements together with Sel-Plex. Key words: feed additives, pork, morphological and biochemical indicators of blood, fattening and slaughter indicators, quality, safety, liver microscopy
Keywords: кормові добавки; свинина; морфологічні та біохімічні показники крові; відгодівельні та забійні показники; якість; безпечність; мікроскопія печінки; feed additives; pork; blood morphological and biochemical parameters; fattening and slaughter performance; quality